Humanitarian Intervention and the Religious Ethos of Japan - Pieroni, Edoardo (Rethinking Asia in World Politics, 2023)
The recent military coup d’état in Myanmar has triggered widespread indignation and concern in the international community. The Tatmadaw have deposed a freely elected government led by the National League for Democracy, interrupting a decade-long process of democratization and repressing the ensuing civil protests with violence. Liberal democracies worldwide issued joint statements of condemnation as well as sanctions targeting the economic interests of the Burmese military. Among them, Japan has been a notable exception in taking significant measures against armed violence. Despite being a democracy pledging to pursue a diplomacy based on freedom, the rule of law and basic human rights, Japan tends to assume passive stances towards violence perpetrated abroad. Drawing from ontological security theory, the article tries to explain this attitude by taking into account Japan’s religious ethos. It is shown that the normative framework underlying Japan’s religious traditions is in stark contrast with the Western, individualistic principles on which humanitarian interventionism is based.